PENGARUH MOTIVASI, STRES KERJA DAN PROMOSI JABATAN TERHADAP KINERJA KARYAWAN PT. ENSEVAL PUTERA MEGATRADING CABANG DENPASAR - Ni Made Ari Mustika Pertiwi; I Wayan Mendra; Tjok Istri Sri Harwathy (EMAS, 2021)
Human resources have a major role in every activity. One of the factors that can affect employee performance is motivation, job stress and job promotion. This study aims to see the effect of motivation, job stress and job promotion on employee performance at PT. Enseval Putera Megatrading Denpasar Branch. The population in this study were 120 people. The sample in this study were 40 employees at PT. Enseval Putera Megatrading Denpasar Branch. Determination of the sample in this study is Probability Sampling, namely simple random sampling, where the researcher provides the same opportunity for each member of the population to be selected as a sample by simple random sampling. The analysis technique used is the instrument test, classical assumption test, inferential test hypothesis test. These results indicate the variable that motivation has a positive and significant effect on employee performance, Job Research has a negative and significant effect on employee performance, and Job Promotion has a positive and significant effect on employee performance at PT. Enseval Putera Megatrading Denpasar Branch.